(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
In this article, the nature and tasks of the export policy and the export management system in the Republic of Uzbekistan are studied. The current state of the development of the textile industry of the Republic of Uzbekistan, the state of export activity has been analyzed. "Konteks Tashkent" LLC has developed practical recommendations on ways to increase the export potential of our Republic.